A Rare Case of Unrecognized and Uncommon Bladder Perforation after Transobturator Tape Procedure - Ercüment Kılınç; Yaşam Kemal Akpak (Case Reports in Medicine)
The transobturator tape (TOT) procedure has become practically widespread worldwide. Complications seem to be rare, but recognizing them intraoperatively is the most significant step because some of the complications which may appear in postoperative period can be challenging for both physicians and patients. The purpose of this case, with this patient who was operated on with open surgery, is to evaluate this rarely seen unrecognized and uncommon bladder perforation after TOT procedure and thus make some contribution to the literature. Here, we present a case report about the treatment of a 48-year-old woman patient with unrecognized and uncommon bladder perforation after TOT procedure, 5 months postoperatively. Cystoscopic evaluation is not recommended routinely, but it must be performed if the patient is complicated enough to create doubt and also the surgeon's skill and ability are not sufficient enough to operate decently.